Relationship of EEG sources of neonatal seizures to acute perinatal brain lesions seen on MRI: A pilot study. Issue 10 (21st April 2012) - Despotovic, Ivana; Cherian, Perumpillichira J.; De, Maarten; Hallez, Hans; Deburchgraeve, Wouter; Govaert, Paul; Lequin, Maarten; Visser, Gerhard H.; Swarte, Renate M.; Vansteenkiste, Ewout; Van, Sabine; Philips, Wilfried
<x xml:space="preserve">Abstract</x> Even though it is known that neonatal seizures are associated with acute brain lesions, the relationship of electroencephalographic (EEG) seizures to acute perinatal brain lesions visible on magnetic resonance imaging (MRI) has not been objectively studied. EEG source localization is successfully used for this purpose in adults, but it has not been sufficiently explored in neonates. Therefore, we developed an integrated method for ictal EEG dipole source localization based on a realistic head model to investigate the utility of EEG source imaging in neonates with postasphyxial seizures. We describe here our method and compare the dipole seizure localization results with acute perinatal lesions seen on brain MRI in 10 full‐term infants with neonatal encephalopathy. Through experimental studies, we also explore the sensitivity of our method to the electrode positioning errors and the variations in neonatal skull geometry and conductivity. The localization results of 45 focal seizures from 10 neonates are compared with the visual analysis of EEG and MRI data, scored by expert physicians. In 9 of 10 neonates, dipole locations showed good relationship with MRI lesions and clinical data. Our experimental results also suggest that the variations in the used values for skull conductivity or thickness have little effect on the dipole localization, whereas inaccurate electrode positioning can reduce the accuracy of source estimates. The performance of our fused method indicates that ictal EEG source imaging is feasible in neonates and with further validation studies, this technique can become a useful diagnostic tool. Hum Brain Mapp 34:2402–2417, 2013. © 2012 Wiley Periodicals, Inc.